A decade of institutionalizing human rights in ASEAN: Progress and challenges. Issue 2 (15th March 2021) - Wahyuningrum, Yuyun
Abstract: The Terms of Reference (TOR) of the ASEAN Intergovernmental Commission on Human Rights (AICHR) include a provision to allow the body to evolve by review every five years. There were huge expectations from civil society that this process would rectify the lack of a protection mandate for human rights. I argue that the TOR review should not be seen as the only way to enable AICHR to evolve. AICHR's evolution can also be accelerated through the development and implementation of its work plans and projects. Furthermore, the ability of AICHR's country Representatives to recognise political opportunities and to creatively interpret AICHR's TOR have significantly strengthened AICHR's ability to promote and protect human rights in the last ten years. Accordingly, this paper examines AICHR's scope and power as stated in its (unreviewed) TOR and the five-year work plans to promote and protect human rights in the region from 2009 to 2019. This paper applies qualitative data collection combining desk research, interviews with key actors, and my own experiences as a human rights activist advocating for human rights in ASEAN since 2008 and as the Representative of Indonesia to AICHR for 2019-2021.